2013
DOI: 10.1378/chest.12-1569
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke and Airway Obstruction in Children With Sickle Cell Anemia

Abstract: Background:The contribution of environmental tobacco smoke (ETS) exposure to pulmonary morbidity in children with sickle cell anemia (SCA) is poorly understood. We tested the hypothesis that children with SCA and ETS exposure would have an increased prevalence of obstructive lung disease and respiratory symptoms compared with children with SCA and no ETS exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Similarly, a retrospective study on lung function data concerning 20 000 children at the age of 6-12 years showed that smoking during pregnancy was independently associated with a lower forced expiratory volume in 1 s (FEV1) (-1--6%) [43]. Similar effects on lung function and the presence of respiratory symptoms at school age have been reported for postnatal exposure to tobacco smoke [44,45]. In a cohort study, passive smoking during the first year of life increased the risk of respiratory symptoms at 5 years of age in children born moderately preterm, with an adjusted odds ratio of 1.8 [45].…”
Section: Second-hand Smoke Exposurementioning
confidence: 66%
“…Similarly, a retrospective study on lung function data concerning 20 000 children at the age of 6-12 years showed that smoking during pregnancy was independently associated with a lower forced expiratory volume in 1 s (FEV1) (-1--6%) [43]. Similar effects on lung function and the presence of respiratory symptoms at school age have been reported for postnatal exposure to tobacco smoke [44,45]. In a cohort study, passive smoking during the first year of life increased the risk of respiratory symptoms at 5 years of age in children born moderately preterm, with an adjusted odds ratio of 1.8 [45].…”
Section: Second-hand Smoke Exposurementioning
confidence: 66%
“…These include a retrospective cohort study of 52 children with SCD that demonstrated an increased rate of hospitalizations in children with exposure by questionnaire [9], a retrospective cohort study that identified an increased risk of ACS (2.6 times) for both primary smokers and adults only exposed to secondhand smoke (exposure assessed via questionnaire) [8], a prospective cohort study that found increased respiratory symptoms and lower airway obstruction in children with SCD (exposure quantified by parental report) [22], and a retrospective cohort study that identified increased ED utilization (73% more visits for ACS) in children with SCD (parental report of secondhand smoke exposure) [23]. The aforementioned studies focused on subjective report of exposure in children's home environments and may not have sufficiently captured other places in which children are frequently exposed to tobacco smoke (such as regular childcare arrangements, the homes of close friends and relatives, or split-parent households) and likely underestimate the effect of tobacco smoke exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These include prophylaxis against influenza (vaccination) and pneumococcal infection (vaccination, penicillin in early childhood) [5], avoidance of exposure to cold water and weather [6], and malaria prophylaxis with bed nets and/or medications in parts of the world where it is endemic [7]. Evidence is mounting that tobacco smoke exposure (TSE), whether first-hand through primary smoking, or secondhand, is a common and important modifiable risk factor for pain [8,9,10], ACS [8,9,10,11,12], and lower airway obstruction [13,14] in children and adults with SCD. …”
Section: Introductionmentioning
confidence: 99%
“…TSE is associated with significant morbidity in children and adults with SCD, whether through secondhand exposure or through primary smoking [8,9,10,11,12,13]. TSE appears to have negative effects on pulmonary function and pulmonary exacerbations of SCD (i.e., more frequent ACS episodes) [8,9,10,11,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation